The Lithic Industry of the Kamyane-Zavallia Linearbandkeramik Site in Ukraine (2019 Campaign) - Kiosak, Dmytro; Dębiec, Maciej; Kolesnychenko, Anzhelika; Saile, Thomas (the Authors, 2023)
The paper treats a selection of lithic finds from Kamyane-Zavallia (Kam’âne-Zavallâ) – the easternmost Linearbandkeramik culture (LBK) site ever excavated. The lithic assemblage belongs to typical representatives of the early farming lithic industries in the region. It is characterized by prismatic cores for blade production, end-scrapers on fragmented blades and flakes, retouched blades, perforators, and a blade fragment with “sickle gloss”. There is a single projectile point of unidentifiable morphology. The authors argue that there is no trace of “Mesolithic heritage” in the assemblage of Kamyane-Zavallia. The assemblage finds close parallels in the sites of Nicolaevca V, Dănceni I, and other LBK sites from Moldova and Romania.
Keywords: Linearbandkeramik; lithic technology; operative chain; trapezes; “Mesolithic heritage”